(untitled) (Research, Society and Development, 2020)
Objective: The present study aimed to discuss the importance of dental treatment in intensive care units for maintaining oral health in patients with systemic disease. Method: A literature review was carried out with a qualitative approach. Were selected scientific articles indexed in the following online databases: Google Scholar and Pubmed. The inclusion criteria were: articles with full availability, documents in Portuguese and English, which were consistent with a theme and publication data between 2012 and 2020. Results: Patients admitted to intensive care units with general health involvement and, often, due to the unfavorable conditions of the oral cavity, they may develop pulmonary and / or generalized infections. The presence of the Dental Surgeon in the interdisciplinary teams of the ICUs contributes to the prevention of nosocomial infections, reducing the length of hospital stay and the use of medicines by the clinical patient, effectively contributing to their well-being and dignity. Conclusion: The related studies, although the presence of dentist is not yet consolidated in the ICUs and the Brazilian legislation still presents gaps for its insertion in the ICU, its importance with the multidisciplinary team is indisputable, considering the simplicity and effectiveness of the measures that make up oral health care procedures.